2017
DOI: 10.1093/toxsci/kfx059
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Chronic Drug Effects on Microengineered Human Liver Cultures Using Global Gene Expression Profiling

Abstract: Global gene expression profiling is useful for elucidating a drug's mechanism of action on the liver; however, such profiling in rats is not very sensitive for predicting human drug-induced liver injury, while dedifferentiated monolayers of primary human hepatocytes (PHHs) do not permit chronic drug treatment. In contrast, micropatterned cocultures (MPCCs) containing PHH colonies and 3T3-J2 fibroblasts maintain a stable liver phenotype for 4-6 weeks. Here, we used MPCCs to test the hypothesis that global gene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 33 publications
0
15
0
1
Order By: Relevance
“…Similar toxicogenomic approaches in MPCC revealed transcriptomic perturbations upon treatment with troglitazone, nefazodone, ibufenac, and tolcapone. Interestingly, the authors found that the number of differentially expressed genes was higher in MPCCs treated with these hepatotoxins compared to those cultures dosed with the corresponding nontoxic analogues (rosiglitazone, buspirone, ibuprofen, and entacapone) …”
Section: Applications Of Advanced Primary Human Hepatocyte Culture Momentioning
confidence: 99%
“…Similar toxicogenomic approaches in MPCC revealed transcriptomic perturbations upon treatment with troglitazone, nefazodone, ibufenac, and tolcapone. Interestingly, the authors found that the number of differentially expressed genes was higher in MPCCs treated with these hepatotoxins compared to those cultures dosed with the corresponding nontoxic analogues (rosiglitazone, buspirone, ibuprofen, and entacapone) …”
Section: Applications Of Advanced Primary Human Hepatocyte Culture Momentioning
confidence: 99%
“…Nowadays, studies have demonstrated the utility of human liver cell-derived micropatterned co-cultures in drug development, including DILI assessment (Khetani et al 2013;Trask et al 2014), yet only few studies have attempted to apply omics technologies to these in vitro culture platforms (Ware et al 2017). Using a micropatterned co-culture model containing PHH and mouse 3T3-J2 fibroblasts, Ware et al explored the hepatotoxic effects of chronic (up to 14 days) and low-dose exposure to several DILI-inducing drugs (Ware et al 2017). The authors found that these hepatotoxins led to a greater number of DEGs in the co-culture modes compared to their non-liver-toxic analogs.…”
Section: Micropatterned (Co-)culture Systemsmentioning
confidence: 99%
“…The authors found that these hepatotoxins led to a greater number of DEGs in the co-culture modes compared to their non-liver-toxic analogs. They also pointed out the transcriptome changes in fatty acid-and drug metabolism-related pathways after troglitazone exposure were responsible for its hepatotoxicity (Ware et al 2017).…”
Section: Micropatterned (Co-)culture Systemsmentioning
confidence: 99%
“…PHH and HepaRG cells in 2D sandwich and 3D spheroid cultures were repeatedly treated with ibuprofen, ibufenac, acetaminophen, and aflatoxin B1 (Sigma-Aldrich, St. Louis, MO). A wide range of concentrations for each chemical was selected based on previous reports 10, 20 that cover relevant concentrations reported in human serum associated with hepatotoxicity.…”
Section: Repeated Compound Exposure and Cytotoxicity Assessmentmentioning
confidence: 99%